30 Years of scientific and pedagogical activity of professor Volodymyr V. Nykyforov - Andrash, Peter (Lviv Politechnic Publishing House, 2019)
For the first time, full data on the scientific and pedagogical work of Professor Volodymyr Nykyforov is published. The main stages of his work for 30 years are considered. The basic results of fundamental research and applied developments of the scientist are discussed.
Keywords: science; higher education; research and developments; biology; ecology; biotechnology